BIOLOGI Crocidolomia pavonana Fabricus (Lepidoptera: Pyralidae) YANG DIPELIHARA DENGAN PAKAN BUATAN DI LABORATORIUM - Ilham, Indri Hendarti, Tris Haris Ramadhan, Nurhadi (Fakultas Pertanian Universitas Tanjungpura, 2019)
Crocidolomia pavonana (F) is one of the Olygophagic pest and is the main pest in family plants (Brassicaceae) which can result in yield loss of up to 65.8%.This study aims to determine the development and reproduction of C. pavonana (F) which is maintained with artificial diets in the laboratory. The Research was carried out in the Tanjungpura University Faculty of Agriculture Plant Pest Laboratory which began from October to January. C. pavonana (F) is preserved in a 50 ml plastic cups.The artificial diets made from Phaseolus vulgaris L. with the addition of other supporting ingredients according to the Salama method (1970).Then do the multiplication of test insects until they reach F2. Furthermore, cohort observations were carried out using 100 individual 1 instars per glass. The parameters observed were life cycle, mortality, sex ratio, fecundity, and egg fertility.The observations were made using 100 instars 1 as individual cohorts per glass .The results showed the development period of C. pavonana (F) from hatching to adult ranged between 24